Предмет: Алгебра,
автор: Аноним
5+2х=0
2х+6=3+5х
5(1-х)+8х= -2-(2х+3)
Ответы
Автор ответа:
0
5+2х=0
2х=0-5
2х=-5
х=-5:2
х=-2,5
2х+6=3+5х
2х-5х=3-6
-3х=-3
х=-3:(-3)
х=1
5(1-х)+8х=-2-(2х+3)
5(1-х)+8х=-2-2х+3
5-5х+8х=1-2х
5+3х=-х
3х+х=-5
4х=-5
х=-5:4
х=-1.25
2х=0-5
2х=-5
х=-5:2
х=-2,5
2х+6=3+5х
2х-5х=3-6
-3х=-3
х=-3:(-3)
х=1
5(1-х)+8х=-2-(2х+3)
5(1-х)+8х=-2-2х+3
5-5х+8х=1-2х
5+3х=-х
3х+х=-5
4х=-5
х=-5:4
х=-1.25
Автор ответа:
0
1). -2.5
2). 1
3). 1.25
2). 1
3). 1.25
Похожие вопросы
Предмет: Қазақ тiлi,
автор: ikohannyj
Предмет: История,
автор: kinezarinka
Предмет: Қазақ тiлi,
автор: kojametovadilbar
Предмет: Математика,
автор: ngnitsyna
Предмет: Литература,
автор: drakosha725